2013
DOI: 10.1109/tvcg.2013.29
|View full text |Cite
|
Sign up to set email alerts
|

Drumming in Immersive Virtual Reality: The Body Shapes the Way We Play

Abstract: Fig. 1. The first person perspective of the participant looking down. (A) in the baseline condition participants were represented by flat shaded white hands. In the between-groups experimental conditions they either had (B) a casually dressed dark-skinned body or (C) a formally dressed light-skinned body. Abstract-It has been shown that it is possible to generate perceptual illusions of ownership in immersive virtual reality (IVR) over a virtual body seen from first person perspective, in other words over a bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
131
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 249 publications
(156 citation statements)
references
References 53 publications
8
131
0
1
Order By: Relevance
“…Aspects such as participant's behavior or their physiology are heavily influenced by the embodiment score (González-Franco et al, 2014;Padrao et al, 2016;Slater and Sanchez-Vives, 2016). The embodiment itself can be modulated by the type, race and look of the avatar participants embody (Hershfield et al, 2011;Kilteni et al, 2013;Peck et al, 2013). Therefore, potentially any manipulation to the participants' avatar might have strong changes on their performance during and after their VR experience.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Aspects such as participant's behavior or their physiology are heavily influenced by the embodiment score (González-Franco et al, 2014;Padrao et al, 2016;Slater and Sanchez-Vives, 2016). The embodiment itself can be modulated by the type, race and look of the avatar participants embody (Hershfield et al, 2011;Kilteni et al, 2013;Peck et al, 2013). Therefore, potentially any manipulation to the participants' avatar might have strong changes on their performance during and after their VR experience.…”
Section: Discussionmentioning
confidence: 99%
“…Embodiment is not only elicited in lookalike or gender/race consistent self-avatars, but is also possible with avatars of a different gender (Kilteni et al, 2013), shape (Yee et al, 2009;Normand et al, 2011;Kilteni et al, 2012b;Won et al, 2015), racial group , or age (Banakou et al, 2013).…”
Section: External Appearancementioning
confidence: 99%
See 1 more Smart Citation
“…By giving participants visual feedback that their real body had been replaced by a mannequin body and providing synchronous tactile simulation, the experiment was able to elicit the illusion of full-body ownership over the mannequin body. This phenomenon has been successfully replicated several times in virtual reality (Slater and Sanchez-Vives, 2014) and various aspects of the illusion have been tested, such as varying the racial appearance of the virtual body (Kilteni et al, 2013;Maister et al, 2013;Peck et al, 2013), limb size (Kilteni et al, 2012), body size (Normand et al, 2011), and also by modifying the age of the virtual body (Banakou et al, 2013). Over several studies, certain factors have been found to have a major effect on the illusion, such as first-person perspective, and the body having a human morphology (Maselli and Slater, 2013).…”
mentioning
confidence: 83%
“…In addition to the questions related to task performance, the visitors were also asked questions related to the BOI and agency twice, once for each robot ( Table 2). The embodiment questionnaire, designed based on a previous study that was carried out using the same robot (Kishore et al, 2014), was not given for VD3 since high ownership illusions and high levels of agency have been reported in various previous studies using the exact same setup (Banakou et al, 2013;Kilteni et al, 2013;Peck et al, 2013). The locals were asked two questions regarding their experience (Table 3).…”
Section: Methodsmentioning
confidence: 99%